Parametric analysis of sound transmission loss in a rectangular duct attached with resonator silencer - Salleh, Muhammad Mohamed; Ghazali, Mohd Hafiz; Md Salleh, Salihatun; Manshoor, Bukhari; Khalid, Amir; Shiau, Wei Chan; Zaman, Izzuddin (Penerbit UINMAP, 2022)
Noise is an existing problem that exist in the environments produced from vibrating sources. In general, the common solutions for noise control are: (1) redesigning the system the system for instance increasing wall thickness or stiffening structures, and (2) adding additional damping in acoustic systems to dissipate sound energy such as the use of resonator silencers. However, the latter is more practical because it does not concern about the complexity of the design and modification cost. In this paper, the application of a single resonator silencer to reduce sound pressure levels and increase transmission loss of a rectangular duct is investigated. The application is further expanded by attaching multiple resonator silencers to study its efficiency. Two types of resonator silencers were analyzed namely quarter wavelength tube (QWT) and Helmholtz resonator (HR), where the sound pressure level and transmission loss were determined by finite element analysis using ANSYS. The first outcomes show that a single HR displays more efficiency in the reduction of sound pressure levels compared to a QWT over a wide frequency range. Subsequently, as the number of resonator silencers increased, the transmission loss was found increase with the sound pressure level decreased simultaneously. Overall, it can be concluded that HR is more effective over a wide frequency range and multiple resonator silencers can increase the transmission loss of rectangular duct.